Microalgae biofuels as an alternative to fossil fuel for power generation - Milano, J. (Elsevier Ltd, 2016)
Biofuels productions from microalgae received wide attention recently and have high potential to replace fossil fuels. This paper served as a platform to critically review current production technologies of microalgae, ranging from cultivation, harvesting, extraction and several biofuels conversion processes. In addition, due to the high photosynthetic efficiency of microalgae, mass cultivation of microalgae is believed to be able to efficiently reduce the carbon dioxide emission to atmosphere and thus, reducing the impact of global warming. This is because microalgae have high growth rate and is able to develop maximum of 70 of lipid content within their cells depending on species. Apart from that, microalgae have the ability to survive under harsh condition and occupied smaller cultivation land area than other land crops. The harvested microalgae biomass can be used for electrical generation, while its crude lipid can be used as transportation fuel as it has 80 average energy content of petroleum. In the present paper, a detailed discussion to produce biodiesel, fuel gas, bio-oil, methane, hydrogen and alcohol from microalgae biomass are also included. Besides, updated research, challenges and the way forward of microalgae biofuels are also presented. In future, biofuels production from microalgae can be economical viable at some scale, which is then profitable in terms of economics and also environment. Â© 2015 Elsevier Ltd. All rights reserved.